The impact of poor cementing casing damage: A numerical simulation study - Hemmatian, M.; Tokhmechi, B.; Rasouli, V.; Gholami, Raoof (SHAHROOD UNIV TECHNOLOGY, 2015)
A good knowledge of the parameters causing casing damage is critically important due to vital role of casing during the life of a well. Cement sheath, which fills in the gap between the casing and wellbore wall, has a profound effect on the resistance of the casing against applied loads. Most of the empirical equations proposed to estimate the collapse resistance of casing ignore the effects of the cement sheath on collapse resistance and rather assume uniform loading on the casing. This paper aims to use numerical modeling to show how a bad cementing job may lead to casing damage. Two separate cases were simulated where the differences between good and bad cementation on casing resistance were studied. In both cases, the same values of stresses were applied at the outer boundary of the models. The results revealed that a good cementing job can provide a perfect sheath against the tangential stress induced by far-field stresses and reduce the chance of casing to be damaged.